Epiphytic algae of Lemna minor L. growing in natural habitat and aquarium - Pala, G.; Selamoglu, Z.; Caglar, M. (Iranian Fisheries Science Research Inst-Ifsri, 2019)
[Abstract Not Available]
Keywords: Lemna minor; Aquarium; Natural habitat; Epiphytic algae